Integrating Reflective, Cognitive, and Technological Dimensions in Early-Stage Translation: Systematic Literature Review - Wulandari Simbolon; Yesa Mutiara Sitompul; Yuli Audyani Hutajulu; Refika Andriani; Tatum Derin (LPPM Universitas Bina Sarana Informatika, 2026)
This study aims to analyze the multifaceted factors that enable novice translators to achieve professional excellence. Using a thematic synthesis approach, the research explores how early translational stages lay the foundation for career growth. The findings reveal that translation is not merely a linguistic function, but a reflective and recursive process influenced by ethical awareness and metacognitive strategies. Recent studies demonstrate that while technological aids like CAT tools and AI-powered systems assist the workflow, they cannot replace human ethical judgment and cognitive abilities. Furthermore, the integration of human-AI synergy is identified as a core professional competence. The study concludes that translation remains a human-focused pursuit that safeguards intellectual integrity amid technological progress. These results advocate for translator curricula that prioritize reflective practices and ethical accountability to prepare emerging practitioners for the evolving digital landscape.